Pengujian Validitas dan Reliabilitas Instrumen Konsepsi Pembelajaran Kimia pada Masa Pandemi COVID-19 Menggunakan Pemodelan Rasch - Hari Sutrisno; Ifan Rivaldo; Alusti Cundo Manik (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine the validity and reliability of students' conception of chemistry learning instruments during the Covid-19 pandemic using Rasch modeling. The developed instrument consists of 24 items tested on 150 students from 3 selected schools classes X, XI, and XII MIPA State Senior High School in Tuban Regency for the 2021/2022 academic year. Two experts tested the content validity of the instrument while the construct validity and item reliability used the Rasch model with Winsteps Rasch software version 3.73. The analysis of the Rasch model used is in the form of item and person separation and reliability, correlation and point measure, Item fit, item rating scale functionality and unidimensionality. The results obtained indicate that the conceptual instrument for chemistry learning that has been developed is valid and reliable. However, the COLS4, COLS6, and COLS11 items are invalid and should be revised or removed